Risk factors of home injury among elderly people in Malaysia - Lim, Kuang Hock; Kaur, Jasvindar; Ibrahim, Normala; Ho, Bee Kiau; Yau, Weng Keong; S., Mohmad; Lai, W. Y.; Mohd Sidik, Sherina (Hong Kong Academy of Medicine Press, 2014)
Background: Home injuries among elderly people are a public health concern. This study aimed to determine the frequency and risk factors of home injuries among elderly people in Malaysia. Methods: The Third National Health and Morbidity Survey in 2006 was carried out from April to July 2006. The sample was proportional to population size and selected in 2 stages. Data were collected through face-to-face interviews using a validated questionnaire. Only injuries occurring within the previous year were included to avoid recall bias. The types of home injury, places where the injuries occurred, ability to work after the injury, and hospital admission were recorded, as were demographic variables such as sex, age, marital status, ethnicity, and residential area. Results: Of 4842 respondents aged ≥60 years, 279 (5.8%) had experienced some kind of home injury within the previous year. The most common types of injury were fall (n=205), cuts (n=43), and being struck by objects (n=14). The most common injury locations were the kitchen (n=81), garden (n=65), bathroom/toilet (n=45), living room (n=26), bedroom (n=22), and stairs (n=21). Home injury rates were significantly higher among women than men (7.4% vs. 3.9%, p<0.001). Married elderly people were less likely to have a home injury than divorced/widowed or single elderly people (4.9% vs. 8.0% vs. 8.0%). Multiple logistic regression analysis revealed that women (adjusted odds ratio [OR]=1.87, 95% confidence interval [CI]=1.37-2.55) and respondents aged 70-74 years (adjusted OR=1.45, 95% CI=1.02-2.07) were more likely to sustain a home injury. Conclusion: With the increase in the elderly population, home injury prevention programmers are urgently needed.